Synthesis and research of automatic balancing system of voltage converter fed induction motor currents - Бойко, Андрей Александрович; Будашко, Виталий Витальевич; Юшков, Евгений Александрович; Бойко, Надежда Анатольевна (Eastern-European Journal of Enterprise Technologies, 2016)
Synthesis of methods for investigating unbalanced operating conditions of thyristor voltage converter fed induction motors is performed. The voltage unbalance factors of the power source are calculated, and the formation conditions are determined. Attention is paid to the harmonic analysis of the induction motor currents. The influence of power source voltage unbalance on the induction motor performance is determined on the basis of simulation and experiments. The results of power source unbalance - phase current unbalance, overload capacity reduction, oscillating nature of torque and speed, dynamics deterioration are outlined. The system of automatic balancing of the induction motor stator currents using the thyristor voltage converter is proposed. The synthesis of the elements of control channels and feedback channels of the balancing system, as well as operation principles, are examined. It is determined that balancing reduces the current unbalance factors by more than an order of magnitude, and virtually ensures the equality of the active stator currents in the induction motor phases. The benefits and drawbacks of the automatic balancing system are presented, and recommendations on its application are given.